The reptiles of South Asia: checklist and distributional summary - Das, I. (Centre for Herpetology, Madras Crocodile Bank Trust, 1994)
A checklist of species and subspecies of reptiles recorded from south Asia is presented. In all, 632 species have been recorded, in 185 genera and 25 families. Endemicity is high, 305 species being restricted to a single physiographic zone and an additional 98 species to more than one zone within the region but not extralimitally. The total endemicity of 403 (63.7%)is high for a chiefly continental landmass.